Analisis Transformasi Tradisi Rentak Kudo di Era Modern di Desa Bintang Marak, Kecamatan Bukit Kerman, Kabupaten Kerinci (Jurnal Pustaka, 2026)
Rentak Kudo is a form of tradition with deep historical significance that is important to the community that supports it. Along with the development of time and the influence of modernization, Rentak Kudo has undergone transformations in terms of its function, meaning, and form of performance. This study aims to examine the transformation of the Rentak Kudo tradition in the modern era in Bintang Marak Village, Bukit Kerman District, Kerinci Regency, as well as to understand how the indigenous community maintains this tradition in the modern era. The research method used in this study is qualitative research with a realist ethnographic approach. The data were obtained through observation and interviews. Interviews were conducted with community members, Ninik Mamak (traditional leaders), and the Head of Bintang Marak Village. The results of the study show that the Rentak Kudo tradition has undergone transformation or change in the modern era. These changes include its function, meaning, and the form of its implementation. Modern society generally understands the function and meaning of Rentak Kudo merely as a form of entertainment performance. However, in reality, Rentak Kudo serves as a traditional ritual function that is only performed at certain times and involves only those directly related to the customary rituals.
Keywords: Transformation; Rentak Kudo; Modern Era